Efficacy of chemotherapy versus chemoradiotherapy for locally advanced endometrial cancer: a systematic review and meta‐analysis - Xiaoyong Xiang; Jing Wang; Zhen Ding (Precision Radiation Oncology, 2021)
Abstract Objective This meta‐analysis evaluates the efficacy of chemoradiotherapy versus chemotherapy in patients with locally advanced endometrial cancer (EC). Methods A systematic search in PubMed, Embase, and the Cochrane Library was performed, according to the PRISMA statement, for the past 10 years to May 28 2020 to identify studies on chemoradiotherapy versus chemotherapy in patients with locally advanced EC. Two independent observers evaluated the identified studies. The obtained data were analyzed using the RevMan 5.3 software. Results Five studies involving 1346 patients with locally advanced EC were identified and included in this meta‐analysis according to the inclusion criteria. All studies reported the recurrence‐free survival, and found that patients who received chemoradiotherapy had a better recurrence‐free survival than those who received chemotherapy only (hazard ratio 1.53, 95% confidence interval 1.01–2.05, P < 0. Data on overall survival were provided in three studies; the meta‐analysis showed that patients who received chemoradiotherapy had a better overall survival than those who received chemotherapy only (hazard ratio 1.80, 95% confidence interval 1.07–2.53; P < 0.001), and their difference was significant. Toxicity details were reported in the Gynecologic Oncology Group‐258 trial. In summary, constitutional symptoms, fatigue, gastrointestinal events, renal or genitourinary events, and musculoskeletal events were more frequent in patients who received chemoradiotherapy, whereas hematological adverse events were more frequent and more severe in those who received chemotherapy only. Conclusions The meta‐analysis showed that patients receiving chemoradiotherapy had a better overall survival and recurrence‐free survival than those who received chemotherapy only. Large‐scale randomized controlled trials are necessary for the future.